ChemInform Abstract: Nickel‐Catalyzed Carboxylation of Benzylic C—N Bonds with CO2. Issue 36 (August 2016) - Moragas, Toni; Gaydou, Morgane; Martin, Ruben
Abstract: An user‐friendly Ni‐catalyzed reductive carboxylation of benzylic C—N bonds with CO2 is described.